A SEMANTIC ANALYSIS OF MODALITY IN THE LYRICS OF TAYLOR SWIFT’S SONGS - Zahro, Vita Fatimatuz; -, As'ari; Sa'diah, Siti (Journal of English Language Teaching and Literature (JELTL), 2024)
Modality is a key semantic category that operates at the sentence level. The purpose of this research is to identify the types of modality and semantic meaning of modality in Taylor Swift’s songs lyrics. The data are all lyrics from five selected songs on Taylor Swift’s Folklore album: August, Cardigan, Mad Woman, Peace and Seven. The method for the research was qualitative content analysis. The results showed 31 modalities, among which were the epistemic modality; necessity (1), and probability (6). Deontic modality; obligation (2). Dynamic modality; Ability (6) and volition (16). Additionally, volition is the semantic meaning of modality that this research indicated to be most dominant. In dynamic modality, volition is the desire to act consciously or intentionally, which requires the individual’s choice and effort. Students and individuals who have a solid understanding of modality are better able to communicate their ideas clearly and modify their communication style in accordance with the situation.